2008
DOI: 10.1029/2008jd009831
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of low amounts of precipitable water vapor by millimeter wave spectroscopy: An intercomparison with radiosonde, Raman lidar, and Fourier transform infrared data

Abstract: [1] Observations of very low amounts of precipitable water vapor (PWV) by means of the Ground-Based Millimeter wave Spectrometer (GBMS) are discussed. Low amounts of column water vapor (between 0.5 and 4 mm) are typical of high mountain sites and polar regions, especially during winter, and are difficult to measure accurately because of the lack of sensitivity of conventional instruments to such low PWV contents. The technique used involves the measurement of atmospheric opacity in the range between 230 and 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…For measuring integrated water vapor (IWV) solar Fourier-transform infrared spectrometry (FTIR) was recently shown to be one of the most accurate and precise ground-based remote sensing techniques (Sussmann et al, 2009) and this has been confirmed by follow-on intercomparison studies (Pałm et al, 2010;Schneider et al, 2010): Table 1 in Sussmann et al (2009) shows that FTIR is comparable with or better than other state-of-the-art IWV sounding techniques, such as GPS, microwave radiometers, Raman lidars, or sun photometers (e.g. Morland et al, 2006;Fiorucci et al, 2008). The precision of FTIR for IWV was estimated to be better than 0.05 mm (2.2 %), and perfect matching to radiosonde response characteristics (scatter plot with slope ≡ 1) could be achieved by applying a dedicated Tikhonov-based spectral inversion scheme to the FTIR data; this retrieval was utilized for a harmonized study of the decadal trends in IWV above the Zugspitze and Jungfraujoch FTIR stations (Sussmann et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…For measuring integrated water vapor (IWV) solar Fourier-transform infrared spectrometry (FTIR) was recently shown to be one of the most accurate and precise ground-based remote sensing techniques (Sussmann et al, 2009) and this has been confirmed by follow-on intercomparison studies (Pałm et al, 2010;Schneider et al, 2010): Table 1 in Sussmann et al (2009) shows that FTIR is comparable with or better than other state-of-the-art IWV sounding techniques, such as GPS, microwave radiometers, Raman lidars, or sun photometers (e.g. Morland et al, 2006;Fiorucci et al, 2008). The precision of FTIR for IWV was estimated to be better than 0.05 mm (2.2 %), and perfect matching to radiosonde response characteristics (scatter plot with slope ≡ 1) could be achieved by applying a dedicated Tikhonov-based spectral inversion scheme to the FTIR data; this retrieval was utilized for a harmonized study of the decadal trends in IWV above the Zugspitze and Jungfraujoch FTIR stations (Sussmann et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…A detailed discussion of the GBMS observing technique and involved equations can be found in de Zafra (1995) and Fiorucci et al (2008).…”
Section: Gbms Observing Techniquementioning
confidence: 99%
“…One valuable source of data has turned out to be groundbased microwave radiometry (e.g., Morland et al, 2006;Fiorucci et al, 2008). Such measurements are being carried out to some extent within the NDACC 1 network, which is dedicated to long-term, ground-based, atmospheric sounding observations at many stations around the globe.…”
Section: R Sussmann Et Al: Trends In Column-integrated Water Vapor mentioning
confidence: 99%
“…The intercomparison data of BASIL (Raman lidar) and GBMS (microwave) with sondes (9th sand 10th row of Table 1) were taken from Fiorucci et al (2008). Both instruments show slopes very close to 1, very small intercepts and biases below 0.1 mm.…”
Section: Comparison To Other Techniquesmentioning
confidence: 99%